Survival and growth of tuatara Sphenodon punctatus following translocation from the Cook Strait to warmer locations in their historic range. Issue 2 (11th March 2020) - Price, Stephanie J.; Grayson, Kristine L.; Gartrell, Brett D.; Nelson, Nicola J.
Abstract: Post-translocation monitoring is fundamental for assessing translocation success and identifying potential threats. We measured outcomes for four cohorts of tuatara Sphenodon punctatus translocated to warmer climates outside of their ecological region, to understand effects of climate warming. Translocation sites were on average 2–4 °C warmer than the source site. We used three short-term measures of success: survival, growth and reproduction. Data on recaptures, morphometric measurements, and reproduction were gathered over 2.5 years following release. Although decades of monitoring will be required to determine long-term translocation success in this species, we provide an interim measure of population progress and translocation site suitability. We found favourable recapture numbers, growth of founders and evidence of reproduction at most sites, with greater increases in body mass observed at warmer, less densely populated sites. Variable growth in the adult population at one translocation site suggested that higher population density, intraspecific competition, and lower water availability could be responsible for substantial weight loss in multiple individuals, and we make management recommendations to reduce population density. Overall, we found that sites with warmer climates and lower population densities were potentially beneficial to translocated tuatara, probably because of enhanced temperature-dependent and density-dependent growth rates. We conclude that tuatara could benefit from translocations to warmer sites in the short term, but further monitoring of this long-lived species is required to determine longer-term population viability following translocation. Future vulnerability to rising air temperatures, associated water availability, and community and ecosystem changes beyond the scope of this study must be considered.